Lives in Transition: Reflections of Syrian Refugee Teachers in Egypt on the Future - Hamuod Alhosin, Rya (AUC Knowledge Fountain, 2026)
The research focuses on the aspirations of Syrian refugee teachers in Egypt. It aims to understand a period in their journey of refuge that is uncertain and dynamic, when they are contemplating the future, aspiring, and planning. This qualitative study will be conducted in Egypt, mainly in New Damietta, Mansoura, and Sixth of October. Since the Syrian revolution started in 2011 as part of the Arab Spring and its evolution into an armed conflict, more than 148,000 Syrian refugees were registered in Egypt with UNHCR in November 2024, while the Egyptian government estimates the number to be much larger. Following the sudden overthrow of Bashar al-Assad and his government on the 8th of December 2024, Syria’s future became central in public discussions. The study will draw on semi-structured interviews with teachers of different ages and backgrounds, with the resulting data analysed thematically to highlight their aspirations for the future. These aspirations go beyond mere wishes; they serve as a form of agency, a reflection of the community’s priorities, challenges, and hopes. By focusing on teachers who have not been previously studied in Egypt, and by following the stories of five Syrian refugee teachers, this research highlights how they envision post-Assad Syria. It explores how their aspirations are shaped by their memories of Syria before the conflict, their lived experiences in exile, and how these perspectives vary across generations and gender. The study also examines how teachers’ professional roles inform their visions for the future, positioning them as intellectuals who contribute to addressing divisions within the social fabric of their communities.